Konstruksi Citra Diri dalam Media Baru melalui Aplikasi Instagram (Analisis Semiotik Postingan Instagram @maudyayunda) - Maslichatus Sholichah; Poppy Febriana (Jurnal Spektrum Komunikasi, 2022)
New media present as communication that individuals choose for social interaction in cyberspace. One of them is Instagram, which is one of the uses of new media in the form of a social media network application that functions as a place to share photos and videos with other users. Instagram makes it easy to form a person's self-image, both positive and negative images in any angle. Like Maudy Ayunda, a public figure who has a good self-image on her Instagram account. This study aims to find out how self-image can be built through Instagram account posts. This type of research is descriptive research with a qualitative approach method that uses a constructivist paradigm with Ferdinand de Saussure's semiotic theory. The results of this study are self-image on the @maudyayunda Instagram account formed from components of verbal and non-verbal messages which can be seen from the description of photo uploads with dress styles and photo styles at certain moments. So from this study it can be concluded that Maudy Ayunda has a personality in building her image that is passionate about learning, intelligent, inspiring, and has a healthy lifestyle.